Evaluation of dimensional change in different elastomeric impression materials used in implants: An original research - Mansi Rajput; J Baranikrishnan; Manawar A Mansoor; Radhika Thakkar; Shivani Karre; Jeetu Verma (Journal of Pharmacy and Bioallied Sciences, 2024)
Aim: The study's objective was to assess the dimensional accuracy of hybrid polyether and polyvinyl siloxane materials for implant impressions. Materials and Methods: Nine groups were created from 45 samples of various building materials and construction techniques from the study. Five samples were tested, and 45 impressions were recorded. Results: The hybrid non-splinted technique has improved implant site replication, accuracy, and low interimplant distance alterations. Conclusion: The finest possible reproduction of implant sites on the master cast was made feasible by the use of an open, non-splinted method and a hybrid polyvinyl siloxane–polyether impression material.